ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN KPRI KARYA DHARMA PAITON - Junaedi, Deddy; Aziz, Adi Yasin Maulana; Junaidi, Ahmad; Khairudin, Imam (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Employee performance is a key indicator of organizational success, especially in cooperative institutions, and one of the determining factors believed to influence performance is work motivation. This study aims to analyze the effect of work motivation on employee performance at Koperasi Pegawai Republik Indonesia (KPRI) Karya Dharma Paiton. The research employed a quantitative approach with a survey method, where primary data were collected through questionnaires distributed to all cooperative employees (total sampling). The research instrument was validated through validity and reliability tests and then analyzed using simple linear regression with SPSS software. The results show that work motivation has a positive and significant effect on employee performance, with a regression coefficient of 0.487 and a significance value of 0.000. This means that the higher the employee’s motivation, the better the performance produced. These findings support Herzberg’s and Maslow’s theories and strengthen previous research, which confirms that both intrinsic and extrinsic motivation consistently play important roles in performance improvement. The study concludes that KPRI Karya Dharma management should place greater emphasis on work motivation strategies to enhance productivity and sustainable performance. The study recommends that the cooperative develop incentive systems, training programs, and employee involvement in decision-making. The limitation of this research lies in its narrow scope, suggesting that future studies expand the coverage and apply mixed-method approaches.